Retraction Note: An apoptosis-enhancing drug overcomes platinum resistance in a tumour-initiating subpopulation of ovarian cancer - D. M. Janzen (Nature Portfolio, 2020)
This Article has been retracted; see accompanying Retraction Note. A previous correction is no longer appended to the PDF version of this paper but can be accessed here: https://doi.org/10.1038/ncomms10703 .